Porous‐Organic‐Polymer‐Triggered Advancement of Sustainable Magnetic Efficient Catalyst for Chemoselective Hydrogenation of Cinnamaldehyde. Issue 14 (3rd June 2020) - Paul, Ratul; Sarkar, Chitra; Yan, Yong; Trinh, Quang Thang; Rao, Bolla Srinivasa; Pao, Chih‐Wen; Lee, Jyh‐Fu; Liu, Wen; Mondal, John
Abstract: In this study, we adopted a cost‐effective, facile and metal & template‐free strategy for the successful synthesis of hydroxyl enriched POP (denoted as TPT). An integrated catalyst, Pd−Fe3 O4 @TPT, has been developed for the liquid phase selective hydrogenation cinnamaldehyde (CAL). Pd−Fe3 O4 @TPT exhibited excellent catalytic performance, providing 100 % selectivity towards hydrocinnamaldehyde (HCAL) under mild reaction conditions (with relatively low hydrogen pressure and very short reaction time), whereas Fe2 O3 @TPT appeared inert. Compared with the conventional catalytic systems, our newly designed catalyst was superior in many aspects, owing to the rigid nature of TPT‐POP, which prevents aggregation and leaching of the metal nanoparticles. Abstract : Porous‐Organic‐Polymer (POP) encapsulated magnetic catalyst (Pd−Fe3 O4 ) exhibited advances in chemoselective hydrogenation of cinnamaldehyde (CAL) to hydrocinnamaldehyde (HCAL, 100 % selectivity), which could be attributed to the formation of Pd−Fe bond with the decrease of Pd−Pd bond distance and flat adsorption of C=C on the Pd surface followed by the contraction of C=O bond as experimentally evidenced with the combination of synchrotron based EXAFS analysis and in‐situ ATR‐IR, DRIFTS spectroscopy studies.